Prevalence of trachoma within refugee camps serving South Sudanese refugees in White Nile State, Sudan: Results from population-based surveys. - Angelia M Sanders; Zeinab Abdalla; Belgesa E Elshafie; Andrew W Nute; Elizabeth F Long; Nabil Aziz; Paul Weiss; E Kelly Callahan; Scott D Nash (Public Library of Science (PLoS), 2019)
Background The world is witnessing mass displacement of populations which could impact global efforts to eliminate neglected tropical diseases such as trachoma. On the African continent, South Sudan has experienced high levels of population displacement. Population based baseline trachoma surveys were conducted among refugee camps in two Sudanese localities hosting South Sudanese refugee populations to determine whether the SAFE strategy was warranted. Methodology/principal findings Cross-sectional, multi-stage, cluster-random surveys were conducted within refugee camps in each of two Sudanese localities, Al Salam and Al Jabalain. For survey sampling, multiple camps within each locality were combined to form the sampling frame for that locality. Household water, sanitation and hygiene indicators were assessed, and trachoma signs were graded by trained and certified graders. The prevalence of trachomatous inflammation-follicular (TF) in children aged one to nine years was 15.7% (95%CI: 12.1-20.2) in Al Salam and 10.6% (95%CI: 7.9-14.0) in Al Jabalain. The prevalence of trachomatous trichiasis (TT) in those 15 years above was 2.9% (95%CI: 1.8-4.8) in Al Salam and 5.0% (95%CI: 3.8-6.6) in Al Jabalain. The presence of water and sanitation was high in both survey units. Conclusion/ significance Sudan has made progress in reducing the prevalence of trachoma within the country; however, the presence of over one million refugees from a neighboring trachoma hyper-endemic country could impact this progress. These surveys were the first step in addressing this important issue. The results demonstrate that at least three years of mass drug administration with azithromycin and tetracycline is needed in addition to the provision of TT surgical services. Additionally, it highlights that non-endemic or formerly endemic localities may have to adopt new strategies to provide services for refugee populations originating from hyper-endemic regions to ensure elimination of trachoma as a public health problem for all populations.